Mapping the potential northern limits and promotion extent of ratoon rice in China. (January 2023) - Yang, Jingya; Hu, Qiong; You, Liangzhi; Cai, Zhiwen; Chen, Yunping; Wei, Haodong; Xu, Zilu; He, Zhen; Yin, Gaofei; Xu, Baodong
Abstract: Ratoon rice has emerged as a promising rice cropping system to improve grain production and reduce labor costs compared with traditional single/double rice in China. However, the potential planting areas of ratoon rice in China remain unclear. This research investigated the potential northern limits and promotion extent of ratoon rice in China by considering its climatic suitability based on the optimized maximum entropy (MaxEnt) model as well as terrain and land use conditions. The MaxEnt model derived by all environmental variables yielded a good performance, with average AUC (area under the curve) and TSS (true skill statistic) over the validation dataset of 0.940 and 0.825, respectively. The comparison with field samples and previous studies revealed the reliability of the derived potential promotion areas. Potential northern limits contained a closed curve surrounding the Sichuan Basin, and the other curve ran from Yunnan Province to Jiangsu Province. Safe promotion areas of ratoon rice in China were 472, 003 km 2, mainly located in Sichuan, Hubei, Guangxi and Hunan. Risky promotion areas were 74, 150 km 2, which were dominant in Henan, Anhui and Yunnan. Our study provides crucial information for rice planting pattern adjustment to alleviate national food insecurity caused by the loss of double rice. Graphical abstract: Image 1 Highlights: Ratoon rice can improve grain production and reduce labor costs. A MaxEnt model was used to map the potential planting areas of ratoon rice. Risky and safe promotion areas are 74, 150 km 2 and 472, 003 km 2, respectively. Northern limits of ratoon rice in China run through ten provinces. Several guidelines for promoting ratoon rice in China were proposed.